Correcting Big Five Personality Measurements for Acquiescence: An 18–Country Cross–Cultural Study. Issue 1 (January 2013) - Rammstedt, Beatrice; Kemper, Christoph J.; Borg, Ingwer
For groups of persons with low or medium levels of education, Big Five personality scales typically yield scores that poorly replicate the idealized Big Five factor pattern. On the basis of representative samples of German adults, Rammstedt et al. have demonstrated that correcting each person's score for acquiescence eliminates this problem. In the present 18–country study using large samples representative of each country's adult population, we found that, in all cases, correcting for acquiescence did indeed improve the congruence of factor loadings with an idealized Big Five pattern. However, although this correction led to acceptably high correspondence levels in all countries classified as individualistic, this was not always true for non–individualistic countries. Possible reasons for this finding are discussed. Copyright © 2012 John Wiley & Sons, Ltd.